Development of digestive system learning application based on discovery learning assisted by augmented reality - Tuti Fatma Rahmawati; Agung Wijaya Subiantoro; Burak Olur (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: The COVID-19 pandemic has caused changes in every sector of life, including the field of education. In addition, students still have difficulty understanding biological concepts in depth during the learning process. This indicates that students' critical thinking skills in biology learning are still low. Objective: The objective of this research is to determine the feasibility and effectiveness level of Augmented Reality (AR) media based on Discovery Learning (DL) on the digestive system material in enhancing students' critical thinking skills and collaboration abilities. Model: This study uses the ADDIE development model. The study was conducted at State Senior High School 1 Srandakan-Yogyakarta, with field trial subjects consisting of 60 students from two classes selected using the cluster random sampling technique. Results: The research results show that the AR media based on DL the digestive system material is deemed suitable for use based on expert assessments, very practical based on the evaluations of biology teachers and students, and effective in enhancing students' critical thinking skills and collaboration abilities based on the MANOVA test results with a significance value of 0.016 (p < 0.05). Conclusion: AR media based on DL can be used as an innovative learning medium to enhance students' critical thinking and collaboration skills in biology education.